THE EFFECT OF TEACHING SKILLS ON THE PERFORMANCE OF TEACHERS OF SDN 44 AMBAN MANOKWARI WEST PAPUA - Sa'adah; Choeroni; Muchtar, Asmaji (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to determine the effect of teaching skills on teacher performance at SDN 44 Amban Manokwari, West Papua. The sample of this study consisted of 20 teachers at the school. This study used a quantitative method with data collection through questionnaires. Based on the results of the T test, it was found that the significance value of the teaching skills variable (X1) was 0.002, which was smaller than the standard error of 0.05, which indicated the influence of teaching skills on teacher performance. The results of the T test showed a calculated t value of 3.708, which was greater than the t table value of 2.10982, which concluded that there was a positive influence of teaching skills on teacher performance. In addition, the results of the normality test using One Sample Kolmogorov-Smirnov showed an Asymp. Sig (2-tailed) value of 0.069 which was greater than 0.05, which meant that the questionnaire data was normally distributed